IMPACT OF ONLINE GAMES ON STUDENT LEARNING MOTIVATION - Prastiwi, Ninda Princess; Pranowo, Taufik Agung (EDUCATIONE, 2023)
Study this aims (1) for knowing impact positive online game to motivation study SMP Negeri 2 Gamping students, (2) Impact negative online game to motivation study SMP Negeri 2 Gamping students, and (3) Services guidance and counseling provided by guidance and counseling teachers in accompaniment students playing online games. Study this use method study qualitative. Method data collection using observation, interview, and documentation. Data obtained then analyzed use descriptive qualitative with steps data reduction, data presentation, and withdrawal conclusion. Test data validity using triangulation source and triangulation technique. Research results this namely (1) Impact positive that arises from use online game to motivation study students at SMP Negeri 2 Gamping that is online game as means entertainment when student fed up with lessons and after learning finished on time rest school, (2) Impact negativity that arises from use online game to motivation study students at SMP Negeri 2 Gamping that is decrease time study student, student be lazy in study, lazy to do Duty so that late gather assignments , students not enough focus in study late come to school because get up oversleep caused play online game until late night so that at school student sleepy in class, so motivation study student decreased, and (3) Guidance and counseling teachers at SMP Negeri 2 Gamping give accompaniment students playing online games and motivation study with give service guidance classic, service guidance groups, and services individual counseling to students, but student not yet feel benefit from accompaniment that and the guardian class no there is collaboration with guidance and counseling teachers in accompaniment students playing online games.